Hello there, and welcome to Brainly!
In this case, x is to be made the subject of the equation, setting x by itself.
Note the equal sign, what you do to one side, you do to the other.
Do the opposite of PEMDAS. PEMDAS is the order of operation, and stands for:
Parenthesis
Exponents (& Roots)
Multiplication
Division
Addition
Subtraction
~
First, subtract n from both sides of the equation:
m (-n) = n (-n) + (x/p)
m - n = x/p
Next, fully isolate the x by multiplying p to all terms on both sides of the equation:
(p) * (m - n) = (x/p) * (p)
p * (m - n) = x
Next, simplify. Distribute p to all terms within the parenthesis:
p(m - n) = x
pm - pn = x
x = pm - pn is your answer.
~